EFFECTIVENESS OF REGISTRATION AND CLASSIFICATION STANDARDS FOR INPATIENTS IN LANGKAT NARCOTICS PRISON - Wilson Santoso Tambun; Rahul Ardian Fikri; Hasdiana Juwita Bintang (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The registration and classification process is a very crucial initial step in the correctional system, its implementation often faces obstacles, both in terms of human resources, facilities, and existing policies. In the context of Langkat Narcotics Penitentiary, where overcapacity and the complexity of narcotics cases are the main problems, the effectiveness of the implementation of prisoner registration and classification standards needs to be further evaluated. This study aims to examine the effectiveness of prisoner registration and classification standards at Langkat Narcotics Penitentiary, as well as how its implementation can support better guidance for prisoners. The data collection tool in this study uses document studies or literature studies, which means searching for data by studying documents or library materials according to the problems being studied. In general, research distinguishes between primary data and secondary data. Primary data is data collected and processed by the researcher directly from the subject or object of the research, while secondary data is data obtained indirectly from the object or subject of the research. These regulations as a whole aim to ensure that every prisoner in Indonesia is properly registered, properly classified according to their characteristics and needs, and receives appropriate guidance to improve their behavior and prepare for their reintegration into society. The implementation of prisoner registration and classification in relation to determining the pattern of guidance in the Correctional Institution (LAPAS) is as important as registration. Overall, proper registration and classification will support the determination of the appropriate pattern of guidance, which in turn can increase the success of rehabilitation and social reintegration of prisoners.